Penerapan Root Cause Analysis (RCA) dalam mengurangi tingkat cacat produk stick lolipop di PT. XYZ - Nasution, Kerina Putri; Fitra, Adi; Insani, Arvita Emarilis (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to identify the root causes of defects in stick lolipop products at PT. XYZ and develop improvement steps using the Root Cause Analysis (RCA) method. The analysis revealed that hole defects were the most dominant type, accounting for 41.7% of total defects. The primary causes include human factors (lack of training and work fatigue), machinery (irregular maintenance and aging machines), materials (low quality raw materials), environment (insufficient ventilation and lighting), methods (setting errors and inadequate SOP supervision), and measurements (limited measuring tools). After implementing improvements such as operator training, periodic machine maintenance, quality enhancement of raw materials, and stricter SOP supervision, the defect percentage decreased by 37.17%.